2016
DOI: 10.12715/har.2016.5.1
|View full text |Cite
|
Sign up to set email alerts
|

Older adults' self-rated health and differences by age and gender: A quantitative study

Abstract: Background:The older adult population is expected to grow, presenting potential challenges for individuals and society. Maintenance of older adults' health will be an important factor for healthy aging. It will also be a challenge for health professionals who work to promote health and care equity. To promote healthy aging and equal care, an overview of older adults' self-rated health is needed. The aim of this study was to describe selfrated health among older adults' living at home describe age group and gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 22 publications
1
18
1
Order By: Relevance
“…Many factors (eg, socioeconomic status, family characteristics, and living arrangement) have been proposed to explain the health inequality among the elderly (7,9,14). In the present study, widowhood of older women might account for the gender differences in psychological health.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Many factors (eg, socioeconomic status, family characteristics, and living arrangement) have been proposed to explain the health inequality among the elderly (7,9,14). In the present study, widowhood of older women might account for the gender differences in psychological health.…”
Section: Discussionmentioning
confidence: 69%
“…Older women in Singapore also had a poorer health status (self-reported health, chronic illness, and functional disability) in comparison with older men (14). Apparently, gender inequalities in health among the elderly in Asia are similar to Western countries, eg, Sweden, Spain, and Italy (7,8,15).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Health problems are perceived as normal, and medical problems are accepted and tolerated without complete loss of the sense of well-being. However, some studies indicate differences between men and women to the health benefit of men [24][25][26] . Josefsson et al [24] also found age differences.…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies indicate differences between men and women to the health benefit of men [24][25][26] . Josefsson et al [24] also found age differences. Older adults aged 65-79, rate their health as relatively good while, hardly surprising, the estimate of quality of health falls from 80-84 years of age.…”
Section: Introductionmentioning
confidence: 99%